Successful elimination of PRRS virus from an infected farrow-to-finish herd by vaccination - M. Toman; V. Celer; J. Smola (Veterinární Medicína, 2017)
Porcine reproductive and respiratory syndrome (PRRS) virus represents a major threat to the swine industry worldwide. This study describes the transmission of a European strain of PRRS-1 to a pig farm leading to the spread of the virus to different age categories of pigs and the development of clinical signs in pregnant sows and piglets. Porcine reproductive and respiratory syndrome aetiology was confirmed by serological tests and by virus isolation and subsequent sequencing. Repeated mass vaccination using modified live virus was used to synchronise the level of PRRS-specific immunity in all age categories of animals and to hinder virus circulation in the herd. Four months after the second mass vaccination, regular modified live virus vaccination of sows and gilts was implemented. Introduction of sentinel animals demonstrated cessation of virus circulation and the success of the control programme.